RQ-AQM: a rate and queue-based active queue management using feedback control theory. (2018) - Bisoy, Sukant Kishoro; Pattnaik, Prasant Kumar
This work proposes a rate and queue based active queue management (RQ-AQM) algorithm to improve the stability of the network system supporting TCP flows. Classical control theory is employed to analyse the stability of TCP/RQ-AQM system and provide systematic guidelines to select control gain parameters of the RQ-AQM. The performance of the proposed algorithm is evaluated and compared with existing algorithms using network simulator-2 (NS2). Simulation results demonstrate that RQ-AQM achieves stability with faster responsive to the dynamic network conditions. The proposed algorithm obtains better performance with respect to throughput, link utilisation, average delay and achieves fastest settling time than others.